Loading cisplatin onto 6-mercaptopurine covalently modified MSNS: a nanomedicine strategy to improve the outcome of cisplatin therapy - Lv X; Zhao M; Wang Y; Hu X; Wu J; Jiang X; Li S; Cui C; Peng S (Dove Medical Press, 2016)
Xiaojie Lv,1 Ming Zhao,1,2 Yuiji Wang,1 Xi Hu,1 Jianhui Wu,1 Xueyun Jiang,1 Shan Li,1 Chunying Cui,1 Shiqi Peng1 1Beijing Area Major Laboratory of Peptide and Small Molecular Drugs, Engineering Research Center of Endogenous Prophylactic of Ministry of Education of China, Beijing Laboratory of Biomedical Materials, College of Pharmaceutical Sciences, Capital Medical University, Beijing, People’s Republic of China; 2Department of Biomedical Science and Environmental Biology, Kaohsiung Medical University, Kaohsiung, Taiwan Abstract: In the treatment of cancer patients, cisplatin (CDDP) exhibits serious cardiac and renal toxicities, while classical combinations related to CDDP are unable to solve these problems and may result in worse prognosis. Alternately, this study covalently conjugated 6-mercaptopurine (6MP) onto the surface of mercapto-modified mesoporous silica nanoparticles (MSNS) to form MSNS-6MP and loaded CDDP into the holes on the surface of MSNS-6MP to form MSNS-6MP/CDDP, a tumor-targeting nano-releasing regime for CDDP and 6MP specifically. In the S180 mouse model, the anti-tumor activity and overall survival of MSNS-6MP/CDDP (50 mg·kg-1·day-1, corresponding to 1 mg·kg-1·day-1 of 6MP and 5 mg·kg-1·day-1 of CDDP) were significantly higher than those of CDDP alone (5 mg·kg-1·day-1) or CDDP (5 mg·kg-1·day-1) plus 6MP (1 mg·kg-1·day-1). The assays of serum alanine aminotransferase, aspartate aminotransferase and creatinine, as well as the images of myocardium and kidney histology, support that MSNS-6MP/CDDP is able to completely eliminate liver, kidney and heart toxicities induced by CDDP alone or CDDP plus 6MP. Keywords: 6-mercaptopurine, cisplatin, mesoporous silica nanoparticles, cancer therapy, nanomedicine